2017
DOI: 10.1097/pcc.0000000000001286
|View full text |Cite
|
Sign up to set email alerts
|

National Variation in the Use of Tracheostomy in Patients With Congenital Heart Disease*

Abstract: Variation in the usage of tracheostomy in infants and children undergoing congenital heart surgery exists across the country. High-tracheostomy centers had lower hospital charges. Late tracheostomy placement, higher congenital heart disease surgical risk, and extracorporeal membrane oxygenation use are independent predictors of in-hospital mortality in this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
41
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(54 citation statements)
references
References 15 publications
12
41
1
Order By: Relevance
“…Surgical procedures, including pediatric tracheostomy, were reported to vary by geographic region. 2,21,22 Our data demonstrate that the geographic variation in rates of pediatric tracheostomy reported by Lewis et al continues to exist, with some regional variation characteristics remaining constant and others shifting over time. As with the Lewis et al study of the 1997 KID, the West had lower tracheostomy rates versus other regions from 2003 to 2012.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Surgical procedures, including pediatric tracheostomy, were reported to vary by geographic region. 2,21,22 Our data demonstrate that the geographic variation in rates of pediatric tracheostomy reported by Lewis et al continues to exist, with some regional variation characteristics remaining constant and others shifting over time. As with the Lewis et al study of the 1997 KID, the West had lower tracheostomy rates versus other regions from 2003 to 2012.…”
Section: Discussionsupporting
confidence: 52%
“…2 The article remains one of few studies to describe national rates, epidemiologic characteristics, and outcomes of pediatric tracheostomies, as subsequent studies largely remained limited to single tertiary referral centers or statewide databases. 3-7…”
mentioning
confidence: 99%
“…Surgical cardiac patients also had a longer intubation time prior to tracheostomy compared with those with all other diagnoses, 36 versus 23 days, which is consistent with previous studies. 5,6 Tracheostomy recipients had no significant difference in morbidity or mortality compared with their long-term intubated counterparts during hospitalization based on abstracted chart review. Four patients who did not receive tracheostomy who were intubated greater than 14 days had signs of upper airway obstruction after extubation, one of these patients required reintubation.…”
Section: Resultsmentioning
confidence: 99%
“…For those who received a tracheostomy, greater inhospital mortality occurred with those requiring extracorporeal membrane oxygenation, higher surgical risk CHD as defined by risk adjustment for congenital heart surgery (RACHS) -1, and later placement of the tracheostomy. 5 Given that these findings determined delayed tracheostomy placement as a risk of higher mortality, further efforts to define indications and timing for tracheostomy, so as to minimize risk but maximize benefit of tracheostomy in congenital heart surgery are warranted. Unfortunately, a major obstacle to such efforts is the lack of standardization in regards to what constitute "prolonged intubation."…”
Section: Discussionmentioning
confidence: 99%
“…15 Johnson et al described that later placement of post-operative tracheostomy in patients with CHD was independently associated with increased odds of in-hospital mortality. 22 In the adult literature, RCTs of tracheostomy after cardiac surgery have revealed that "early" tracheostomy is associated with decreased mortality rates, fewer unscheduled extubations, and more sedation-free days. The decision, timing, and anticipated post-HTx hospitalization outcomes for performing a tracheostomy in a child awaiting HTx should be considered on a case-by-case basis and should be influenced by the indication for tracheostomy.…”
Section: Discussionmentioning
confidence: 99%